The Effect of Dumbbell Training and Rubber Weight Training on Badminton Smash Shots - Ishak, Muhammad; Hakim, Hikmad; Syahruddin, Syahruddin (Universitas Pendidikan Indonesia, 2024)
This research aims to determine: the effect of dumbbell training and rubber weight training on the ability to hit smash in badminton at BKMF FIK UNM. The population of this study were all badminton players or members of BKMF FIK UNM with a total research sample of 20 players. The system is divided into groups. The research results show that; (1) From the summary results of the table, the observation value = 9.032 ttable = 1.729 at the 95% significance level (a = 0.05). So Ho is rejected and Hl is accepted, meaning there is a difference between the initial test and the final test. So there is an influence of dumbbell training on smash shot ability in badminton at BKMF Badminton FIK UNM. (2). From the summary results of the table, the observation value = 8.128 t table = 1.729 at the 95% significance level (a= 0.05). The conclusion is that there is a significant influence of rubber weight training on smash shot ability in badminton at BKMF Badminton FIK UNM. (3). From the summary results of the table, the observation value = 3.368 ttable = 2.101 at the 95% significance level (a=0.05). So Ho is rejected and Hl is accepted, meaning there is a difference in the form of training with rubber weight training.